Hydrogen concentration measurements using a gel-filled electrochemical probe - Allcock, Bryan W. (Cranfield University, 1993)
A novel gel-filled electrochemical hydrogen probe was developed and used to measure hydrogen concentrations in carbon-manganese steels. The results were compared with those from an electrochemical permeation technique and a volumetric method. The probe was used to determine the distribution of hydrogen in 5mm steel plates cathodically charged on one side to represent the wall of a pipe or pressure vessel used in hydrogen service. The concentration measurements obtained by the three techniques were in good agreement with each other and with those predicted from diffusion equations and this permitted the precise boundary conditions on the charged metal surface to be determined. Surface reaction kinetics were investigated to model the hydrogen distribution and these were solved using solutions to Fick's diffusion equations. After long charging times the hydrogen concentration on the efflux surface of the plate approached that on the influx side, indicating that an almost uniform hydrogen distribution had been established. Rather than rapid loss of hydrogen from the free surface, as had been assumed previously, it was clear that there was a large resistance to hydrogen transport across the metal/air interface. Microstructural damage was examined both optically and using the scanning electron microscope. Separate investigations were carried out to help understand the effect that reversible and irreversible trapping had on the diffusion of hydrogen through the steel.